PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT PERKEBUNAN NUSANTARA IV (PERSERO) UNIT USAHA PABATU - Yulia Andini; Yusniar Lubis; Rahma Sari Siregar (Jurnal Agriuma, 2019)
This study was conducted to determine the effect of  work discipline on employee productivity at PT. Perkebunan Nusantara IV (Persero) Pabatu Business Unit. The population in this study were all employees of the department, engineering / processing,  and  general  at  PT. Perkebunan Nusantara IV (Persero) Unit Business Unit is 1031 people. the number of respondents used in this study were 104 people. The research was obtained from the results of the t test on the variables obeying all company regulations, namely 2.652> T table = 1.980 stating that complying with all company regulations had a positive and significant effect on employee work productivity. Effective use of time is 3,069 <Ttable = 1,980 stating that  effective use of time has a positive and significant effect on employee work productivity variables. Responsibility for work and assignments is 5,467> T table = 1.980 states that work responsibilities and tasks have positive and significant to employee work productivity. The absentee level of 1,200 <Ttable = 1,980 has a positive and insignificant effect  on employee work productivity. The simultaneous test results obtained are 262.880> 2.31, which states that work discipline simultaneously has a positive and significant effect on employee work productivity. And the R value obtained is 0.884. This figure shows that 88.4% of work productivity is explained by the variable work discipline.